Development of nano-order powder via electrospray - Naim, Mohd Nazli; Abu Bakar, Noor Fitrah; Tan, Kah Boon; Saallah, Suryani (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Nano-order particles have recently being utilized for uniform surface coating and thin film production in food, biomedical and pharmaceutical applications due to their high specific surface area. In this study, production of nano-order particles from Zinc Oxide (ZnO) powder using electrospray method was developed. ZnO suspensions of different pH were prepared by dispersing ZnO powder in distilled water followed by sonication. The zeta potential value and particle size distribution of the prepared ZnO suspensions were in the range of-17 to -53 mV and 104-197 nm respectively. Electrosprayed ZnO suspensions were maintained under Taylor cone mode by manipulating the voltage supply in order to obtain stable and monodisperse droplets. Scaling law models were used to determine the theoretical mean droplet size based on conductivity value of the suspensions. The collected droplets were analyzed visually with scanning electron microscope (SEM). The results showed that mean droplet size obtained from this experiment was smaller than the theoretical ones and strongly dependent on suspension conductivity. Findings of the present study also confirmed that electrospray is a promising approach for producing nano-order particles.